Behavioral and Neurophysiological Effects of Transdermal Rotigotine in Atypical Parkinsonism - Moretti, Davide Vito; Binetti, Giuliano; Zanetti, Orazio; Frisoni, Giovanni Battista (Frontiers in Neurology, 2014)
Effective therapies for the so-called atypical parkinsonian disorders (APS) such as multiple system atrophy (MSA), progressive supranuclear palsy (PSP), or corticobasal syndrome (CBS) are not available. Dopamine agonists are not often used in APS because of inefficacy and, in a minority of case, their side effects, like dyskinesias, impairment of extrapiramidal symptoms or the appearance of psychosis and REM sleep behavioral disorders. (RBD). Transdermal rotigotine (RTG) is a non-ergot dopamine agonist indicated for use in early and advanced Parkinson’s disease with a good tolerability and safety. Moreover, its action on a wide range of dopamine receptors, D1, D2, D3, unlike other dopamine agonists, could make it a good option in APS, where a massive dopamine cell loss is documented. In this pilot, observational open-label study we evaluate the efficacy and tolerability of RTG in patients affected by APS. 32 subjects with diagnosis of APS were treated with transdermal RTG. APS diagnosis was: multiple system atrophy parkinsonian type (MSA-P), multiple system atrophy cerebellar type (MSA-C), PSP, CBS. Patients were evaluated by UPDRS-III, NPI, MMSE at baseline and after 6, 12 and 18 months. The titration schedule was maintained very flexible, searching the major clinical effect and the minor possible adverse events at each visit. Adverse events were recorded. APS patients treated with RTG show a overall decrease of UPDRS III scores without increasing behavioral disturbances. Only 3 patients were dropped out of the study. Main adverse events were hypotension, nausea, vomiting, drowsiness, tachycardia. The EEG power spectra analysis shows a decrease of theta and an increase of low alpha power. In conclusion, transdermal RTG seems to be effective and well tolerated in APS patients.